Surgical Treatment of SplenicFlexure Colon Cancer: Analysisof Short-Term and Long-Term Outcomes of Three DifferentSurgical Procedures - Huang, Mingjin; Wang, Xiaojie; Shao, Yu; Huang, Shenghui; Huang, Ying; Chi, Pan (Frontiers in Oncology, 2022)
Background The aim of this study was to compare the short- and long-term outcomes of splenic flexure colectomy (SFC), left hemicolectomy (LHC) and extended left hemicolectomy (ELHC) for splenic flexure colon cancer. Methods Between January 2011 and December 2018, 117 patients with splenic flexure cancer were enrolled in the study. We retrospectively compared the postoperative, pathological and long-term outcomes of patients with splenic flexure cancer. Results Of the 117 patients, 73 (62.4%) underwent SFC, 22 (18.8%) underwent LHC, and 22 (18.8%) underwent ELHC. No statistically significant differences were found among the groups regarding postoperative complications, pathological data or recurrence. No metastatic lymph nodes at the root of the inferior mesenteric artery (IMA) were observed; lymph node metastasis appeared at the root of the middle colic artery (MCA), but in a low proportion of cases (4.4%). Looking at long-term prognosis, no differences were observed among the three groups regarding both 5-year overall survival (94.0% vs 90.2% vs 94.1%) and disease-free survival (88.2% vs 90.2% vs 83.0%). Conclusion Our retrospective review suggests that splenic flexure colectomy in minimally invasive surgery is a safe and effective treatment option for splenic flexure colon cancer. The rate of metastatic lymph nodes at the root of the central artery and gastroepiploic arcade node was relatively low.